Brand interpretation model. Images and perceptions - Neves, Ronaldo Mendes (2014)
This study presents a brand interpretation model in order to contribute to deepen the knowledge on the methodological research procedures used in strategic and organizational communication. Brand communication (Aaker, 1998; Keller, 2006; Ruão, 2006; Batey, 2010) is built upon a series of promotion activities that generate a set of mental perceptions or images in the public. These perceptions are composed of attributes related to the human capacity of recognition and approval of brand elements. To analyze these dimensions of brand perceptions, we enclosed the mental components (of vision and recall) in order to interpret the rational, emotional end symbolic indicators of memory and acceptance. To do so, we adapted the image configuration method (De Toni, 2009) to the awareness research (Ruão et al, 2013), and we developed a model of brand interpretation, characterized of three procedures: 1) data collection on brand attributes and perception indicators; 2) classification of recognition rate or brand awareness level; and 3) identification of the degree of approval of brand elements. It is noteworthy; that this qualitative research is part of a PhD project in communication sciences. As we believe that the brand interpretation model can be helpful to the decision process on the elements that should be of part of the brands, taking place in companies. Therefore, we emphasize that this model can be an innovative contribution to research development on corporate brand communication.